The Role of SHOX Gene in Short Stature of Turner Syndrome and Its Variant - Tri Indah Winarni; Farmaditya EP Mundhofir; Sultana MH Faradz (MEDIA MEDIKA INDONESIANA, 2010)
Background: SHOX gene is located on the edge of each short/p arm sex chromosome called the pseudoautosomal region-1 (PAR1) plays as a fundamental role on controlling chondrocyte differentiation and apoptosis in the growth plate. Longitudinal growth is determined by environmental, hormonal and genetic factors. Short stature is defined as a standing height below the third percentile according to Tanner et al. Short stature affects approximately 2% of children. Turner syndrome is the most common genetic disorder in female characterized by the absence of all or part of a normal second X chromosome, affecting 1:2500 live-born female babies. Short stature and ovarian failure is the main clinical feature. The objective of this study is to elucidate the implication of SHOX gene in short stature of Turner Syndrome and its variant.Method: Purposive sampling was performed to recruit female with short stature after informed consent agreement. Female with growth treatment history and chronic diseases was excluded from this study. Cytogenetics testing was done for all samples by G-banding method, in routine karyotyping. Result: We report 9 females with short stature which cytogenetically and clinically diagnosed as Turner Syndrome. Four cases is classic Turner syndrome with standing height is below third percentile, three cases are 45,X/46,X,i(Xq) with standing height is below third percentile, one case is 46,XX/45,X (80%) with standing height is below third percentile, and the rest is 46,XX/45,X (20%) with standing height is between 3rd–97th percentile or normal.Conclusion: SHOX gene haploinsufficiency is strongly indicated the cause of short stature in Turner Syndrome.ABSTRAKPeran gen SHOX pada perawakan pendek Sindrom Turner dan variannyaLatar belakang: Gen SHOX terdapat di ujung lengan pendek kromosom seks yang disebut pseudoautosomal regio-1 (PAR1) yang berperan penting pada pengaturan diferensiasi kondrosit and apoptosis di lempeng epifisis. Pertumbuhan memanjang ditentukan oleh faktor lingkungan, hormon, dan faktor genetik. Menurut Tanner dkk, perawakan pendek didefinisikan sebagai tinggi badan kurang dari tiga persentil dan diperkirakan terjadi pada 2% populasi anak-anak. Sindrom Turner merupakan kelainan genetik pada perempuan yang paling banyak ditemukan akibat hilangnya sebagian atau seluruh kromosom X normal yang kedua dengan gambaran klinik utama berupa short stature dan insufisiensi ovarium, dengan insidensi 1:2500 bayi lahir hidup. Tujuan penelitian ini untuk memahami peran gen SHOX pada perawakan pendek Sindrom Turner dan variannya.Metode: Subjek penelitian adalah wanita berperawakan pendek yang setuju mengikuti penelitian dengan menandatangani informed consent. Dilakukan eksklusi untuk wanita berperawakan pendek dengan riwayat pengobatan pemacu pertumbuhan dan penyakit kronik. Pemeriksaan sitogenetik dengan metode pengecatan Giemsa dilakukan pada semua preparat kromosom dilanjutkan dengan analisis kromosom rutin.Hasil: Dilaporkan sembilan (9) wanita berperawakan pendek yang secara sitogenetik dan klinis didiagnosis sebagai Sindrom Turner. Empat kasus didiagnosis sebagai Sindrom Turner klasik dengan tinggi badan di bawah tiga persentil, tiga kasus dengan 45,X/46,X,i(Xq) dengan tinggi badan di bawah tiga persentil, satu kasus dengan 46,XX/45,X (80%) dengan tinggi badan di bawah tiga persentil, dan sisanya adalah 46,XX/45,X (20%) dengan tinggi badan di bawah antara 3-97 persentil atau normal.Simpulan: Haploinsufficiency gen SHOX diduga kuat menyebabkan perawakan pendek pada Sindrom Turner.